Protective effect of hydroalcoholic extracts of Trifolium pratense L. on pancreatic β cell line (RIN-5F) against cytotoxicty of streptozotocin - Mozafar Khazaei; Mona Pazhouhi (Research in Pharmaceutical Sciences, 2018)
Natural plants have traditionally been used throughout the world for their anti-diabetic effects. The aim of the present study was to investigate the protective effect of hydroalcoholic extract of Trifolium pratens L. (T. pratense) on streptozotocin (STZ) cytotoxicity and insulin concentration from RIN-5F pancreatic β cell line. In this study, possible cytoprotective action of T. pratense extract (using pre-treatment, simultaneous, and post-treatment schedules) against STZ (30 mM) was evaluated using MTT assay. Apoptosis was quantified by fluorescent dye staining. Also, the effect of extract on insulin secretion in low and high glucose media was examined. Data were analyzed by one-way ANOVA test and P < 0.05 was considered significant. The viability of RIN-5F cells in 10, 20, 30, 40, and 60 μg/mL doses of T. pratense extract showed significant increases compared to control group (P < 0.001). STZ significantly reduced cell viability in a dose-dependent manner (P < 0.05). T. pratense extract in 20, 30, and 40 μg/mL doses had significant cytoprotective effect (P < 0.05) on cytotoxic action of STZ and this effect is greater in simultaneous treatment. STZ-mediated apoptotic death is reduced by extract. T. pratense extract treatment also, increased insulin concentration in cell culture medium. T. pratense had potent cytoprotective action, prevented apoptosis and increased insulin concentration in cell culture medium via the increase in pancreatic β cell number and/or insulin secretion. In addition, T. pratense enhanced viability of RIN-5F. Thus, T. pratense not only has anti-diabetic actions on β cells but also enhances their viability.